Voluntary Consent: Why a Value-Neutral Concept Won’t Work - Wertheimer, Alan (Oxford University Press, 2012)
Some maintain that voluntariness is a value-neutral concept. On that view, someone acts involuntarily if subject to a controlling influence or has no acceptable alternatives. I argue that a value-neutral conception of voluntariness cannot explain when and why consent is invalid and that we need a moralized account of voluntariness. On that view, most concerns about the voluntariness of consent to participate in research are not well founded.